Oligomer Formation Propensities of Dimeric Bundle Peptides Correlate with Cell Penetration Abilities - Hyun, Soonsil; Lee, Yuno; Jin, Sun Mi; Cho, Jane; Park, Jeemin; Hyeon, Changbong; Kim, Key-Sun; Lee, Yan; Yu, Jaehoon (AMER CHEMICAL SOC, 2018)
LK-3, an amphipathic dimeric peptide linked by two disulfide bonds, and related isomeric bundles were synthesized, and their cell penetrating abilities were investigated. The measurements using size exclusion chromatography and dynamic light scattering show that LK-3 and its isomers form cell penetrating oligomers. Calculations, performed for various types of peptide isomers, elucidate a strong correlation between the amphipathic character of dimers and cell penetration ability. The results suggest that the amphipathicities of LK-3 and related bundle dimers are responsible for their oligomerization propensities which in turn determine their cell penetrating abilities. The observations made in this study provide detailed information about the mechanism of cell uptake of LK-3 and suggest a plausible insight of the early stage of nanoparticle formation of the cell penetrating amphipathic peptides.